THE POTENTIAL OF KALANGKALA (Litsea angulata) SEED EXTRACT AS A NATURAL SPERMICIDE MATERIAL - Akmal, Rommy; Rusmiati, Rusmiati; Santoso, Heri Budi (TROPICAL WETLAND JOURNAL, 2017)
Kalangkala (Litsea angulata) is one of the endemic plants in the wetlands area inKalimantan which seeds are can reduce the quality of male mice spermatozoa such as motility and mobility. The purpose of this research is to know the potential of kalangkala seed extract on other parameters of spermatozoa quality, which are viability and morphology of male mice spermatozoa in an effort to obtain natural spermicide material. This research used five treatments by using twentyfive male mice. The design of this research was spermatozoa suspensions without being treated (Control = 0), spermatozoa suspensions +Na-CMC 0,5% (P1), spermatozoa suspensions + extract of kalangkala seed 0,1% (P2), spermatozoa suspensions + extract of kalangkala seed 0,3% (P3), and spermatozoa suspensions + extract of kalangkala seed 0,5% (P4), with five repititions for each treatment. The result of this research showed that thekalangkala seed extract reduce the percentage of viability of spermatozoa and increased the percentage of abnormal morphology of spermatozoa male mice. Therefore, kalangkala seed extract has potential as a natural spermicide.